A hydrogel-actuated microvalve for smart flow control - Lei, Ming; Wan Salim, Wan Wardatul Amani; Siegel, Ronald A.; Ziaie, Babak (IEEE, 2004)
In this paper, we report on the fabrication and testing of a hydrogel-actuated smart microvalve for biomedical applications. The three-layered microvalve is composed of a stimuli-sensitive ìintelligentî hydrogel sandwiched between a porous silicon membrane and a bossed PDMS flexible diaphragm. The entrapped hydrogel in response to changes in the external physiological stimuli (e.g., pH, glucose, etc.), which diffuses through the porous membrane, swelles and deswelles hence deflecting the flexible PDMS diaphragm and controlling the closure and opening of the microvalve inlet. A microvalve incorporating a 155µm thick hydrogel (poly(methacrylic acid-co-acrylamide), mAA-co-AAm) has a response time of 3.6 min to a sudden pH change (pH=3 to pH=7).